Intervention into the development of currency exchange rates and prosperity of economy - Kraft, Jiří (Univerzita Pardubice, 2015)
The stagnation in economic growth is a problem of developed market economies. Its cause may be a lack of demand caused by the phenomenon of deflation. In addressing these issues monetary policy instruments are offered to use. The prosperity of a small open economy, however, in today's globalizing world, is strongly influenced by the development of relevant foreign economies. Reducing the exchange rate of the national currency may lead to an increase in the price level, and thus solve the problem. Such a step was taken CNB (Czech National Bank) in November 2013. The aim of this article is to assess whether the CNB intervention to the detriment of the exchange rate of the CZK has contributed to increasing prosperity of the Czech economy. The evolution of the exchange rate CZK/EUR is being analysed on the one hand, and on the other the developments in the GDP, exports and imports, and their relationships, using the sensitivity rate, regression analysis and comparison of standardized values within 20 quarterly periods in 2010-2014. The results show that after CNB intervention, there has been a noticeable growth in GDP, while exports grew with a higher dynamics than imports.
Keywords: central bank intervention; exchange rate; gross domestic product; export; import; Czech economy; E58; E61